Optimasi Susunan Bahan Makanan untuk Ibu Hamil Kurang Energi Kronis (KEK) Menggunakan Algoritme Genetika - Ika Oktaviandita; Imam Cholissodin; Putra Pandu Adikara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Women during pregnancy are advised to maintain nutritional adequacy, especially energy and protein. Inadequate nutrition intake will cause pregnant women at risk of Chronic Lack of Energy or in Indonesian called as Kurang Energi Kronis (KEK). In this research given recommendations of the composition of foodstuffs that have balanced nutrition with minimal price using genetic algorithm. The process of finding a solution is to perform a combination of chromosomes and then processed using genetic operators (crossover, mutation, and selection). Crossover process using one cut point method, mutation method used is exchange mutation, and selection process using selection elitism method. Need of parameters of genetic algorithm are population size, Crossover rate (Cr), Mutation rate (Mr), and number of generations. In this system obtained the best optimization results on the population size of 100 population with average fitness value 17.744, Cr value of 0.5 and the value of Mr of 0.5 with average fitness value 17.983, and on the number of generations 100 generated average Average fitness value of 17.962. The results obtained recommendations of the composition of foodstuffs for 7 days along with the costs to be incurred. However, these results still do not meet the maximal needs during pregnancy.